Sugar palm starch biopolymer: extraction and processing - Sahari, J.; Maleque, Md. Abdul; Sapuan, S. M. (CRC Press, 2019)
Increasing awareness about environmental issues has led to a growing interest in using polymers derived from renewable sources that are generally biodegradable. Biopolymers have attracted tremendous attention due to their environmental advantages and the realization of the limited amount of petroleum resources. It is known that renewable resources such as plants, (cellulose or chitin, and vegetable oils), bacteria, as well as non-renewable petroleum (e.g., aliphatic/aliphatic-aromatic co-polyester) are sources of a variety of polymeric materials. Cellulose is the main skeletal component in plants, and polysaccharide cellulose is an almost inexhaustible polymeric raw material with fascinating structure and properties .Native cellulose is widely distributed in nature. It is the main component of cotton, kapok, flax, hemp, jute, ramie, and wood. Cellulose is not found in a pure form, but cotton contains the purest form of cellulose. It can be produced via lactic acid from fermentable sugar. It is also one of the most famous biodegradable polyesters with many excellent properties, and it has been widely applied in many fields. PLA has demonstrated good biocompatibility and is easily processed, as well as high strength and modulus. However, PLA is very brittle under tension and bending loads and develops serious physical aging issues during application. The packaging industry today is focusing on the design and development of new materials using natural resources. These new generations of biobased products are becoming essential alternatives to reduce the dependency on petroleum-based materials.